Between Educational Freedom and Technocratic Trap: The Philosophical Implications of the Merdeka Belajar Policy in Indonesia - Yuliantoro, Moch Najib; Murtiningsih, Siti; Budiani Trisakti, Sonjoruri (Universitas Gadjah Mada, 2026)
This article examines the Merdeka Belajar policy as a value-laden practice within Indonesia’s education reform, emphasizing its philosophical and cultural implications for primary and secondary education. Rather than treating the policy as a technical innovation, this study explores the underlying values, assumptions, and normative tensions that shape its orientation. The study employs a qualitative approach through conceptual and philosophical analysis based on policy documents, educational philosophy, and contemporary social theory. The analysis focuses on how the policy frames educational freedom, pedagogical autonomy, and the relationship between education and culture. The findings indicate that Merdeka Belajar holds emancipatory potential in promoting pedagogical autonomy, contextual learning, and student-centered education. However, it also reveals tensions between educational freedom and technocratic tendencies, which may reduce education to an instrumental function. This study highlights that Merdeka Belajar should be understood as a cultural project that integrates pedagogical flexibility with ethical and cultural orientation, contributing to social cohesion and community well-being.